Abdominal aortic aneurysm: novel mechanisms and therapies. (November 2015) - Unknown
Abstract : Purpose of review: Abdominal aortic aneurysm (AAA) is a pathological condition of permanent dilation that portends the potentially fatal consequence of aortic rupture. This review emphasizes recent advances in mechanistic insight into aneurysm pathogenesis and potential pharmacologic therapies that are on the horizon for AAAs. Recent findings: An increasing body of evidence demonstrates that genetic factors, including 3p12.3, DAB2IP, LDLr, LRP1, matrix metalloproteinase (MMP)-3, TGFBR2, and SORT1 loci, are associated with AAA development. Current human studies and animal models have shown that many leukocytes and inflammatory mediators, such as IL-1, IL-17, TGF-β, and angiotensin II, are involved in the pathogenesis of AAAs. Leukocytic infiltration into aortic media leads to smooth muscle cell depletion, generation of reactive oxygen species, and extracellular matrix fragmentation. Preclinical investigations into pharmacological therapies for AAAs have provided intriguing insight into the roles of microRNAs in regulating many pathological pathways in AAA development. Several large clinical trials are ongoing, seeking to translate preclinical findings into therapeutic options. Summary: Recent studies have identified many potential mechanisms involved in AAA pathogenesis that provide insight into the development of a medical treatment for this disease.